Raja - Doillon, Jacques; Louvart, Hélène; Greggory, Pascal; Benssallem, Najat; Abdelwahed, Ilham (Film Movement, 2006)
Jacques Doillon's supremely written, remarkably acted "Raja" is a romantic tug-of-war that brings to mind both a Shakespearean comedy of errors and Bernardo Bertolucci's undervalued interracial smackdown "Besieged". The director's eponymous heroine goes to work with her cousin at a pasha in Morocco owned by a lazy, intellectual Frenchman. The suave, persistent Fred (Pascal Greggory) is drawn to her ordinariness and the 19-year-old Raja (Najat Benssallem) is smitten by his sexiness. Their innocent crush quickly escalates into a war of bitter jealousies, sparring libidos, and brutal miscommunications. Neither can speak each other's language, and as such they turn to others to translate for them. Doillon illuminates Fred's worldview via a series of unnervingly jolly discussions with two portly female cooks who could pass for happy-go-lucky relatives of the three Macbeth witches, but the perpetually laughing women are smarter than meets the eye. They're clearly fond of Fred, but that one of them deliberately miscommunicates Raja's words and intentions suggests that they are mindful of the dangerous power struggle implicit in his affections for the young girl. Doillon makes excellent use of widescreen. His airy, deceptively simple compositions frequently isolate Greggory and Benssallem to either side of the frame, emphasizing the wide economical and cultural split that exists between the two. [www.slantmagazine.com]